Caracterização do inflamassoma NLRP3 na neoplasia intraepitelial cervical associada à infecção pelo Papilomavírus Humano (HPV) - Raquel Rodrigues Martins (2018)
Cervical cancer remains an important public health problem in women worldwide and in Brazil. In the 2016/2017 biennium alone, there were about 16,340 new cases of cervical cancer in the country. This cancer is preceded by cervical intraepithelial neoplasia (CIN), which develops mainly from the complex relationship between persistent Human papillomavirus (HPV) infection and chronic inflammation in the squamous mucosa of the uterine cervix. In the context of this relationship, inflammassoma, a cellular signaling platform that activates pro-inflammatory factors, has been associated with viral infection and cancer development. However, the involvement of inflammassoma in cervical carcinogenesis is unknown. Thus, this work aims to characterize the inflammassoma in the CIN associated with HPV infection, particularly in keratinocytes, which may contribute to the construction of new knowledge and selection of biomarkers with clinical utility. A descriptive study of the immunohistochemical immunoreactivity (IHC) of the biomarkers NLRP3, caspases-4/5 and 1 and interleukins (IL) 1 and 18 in 35 biopsies of the uterine cervix with diagnoses of nonspecific cervicitis (n = 11), CIN1 (n = 14) and CIN2 / 3 (n = 10), and in 25 cell blocks from cytology in the uterine cervix and diagnosed with inflammation (n = 12) and low squamous intraepithelial lesions (LSIL; n = 7) and high (HSIL; n = 6). HPV detection was performed by IHC and polymerase chain reaction (PCR).The NLRP3and caspases-4/5 expressions were strong or elevated in NIC2/3 and weak or basal in NIC1. In addition, NLRP3 epithelial expression was associated with HPV. Taken together, these results evidence the relationship of HPV with NLRP3 inflammassoma in intraepithelial neoplasia of the cervix.